THE IMPLANTATION OF CHARACTER VALUES TOWARD STUDENTS THROUGH CONGKAK GAME FOR MATHEMATICS INSTRUCTIONAL MEDIA - Agusti, Fardatil Aini; Zafirah, Afifah; Engkizar, Engkizar; Anwar, Fuady; Arifin, Zainul; Syafril, Syafrimen (Jurnal Penelitian Pendidikan, 2018)
This research aims to investigate character values that can be applied on students through congkak game as it is used as a media of mathematics learning. This study used qualitative and quantitative combination or (Exploratory mixed methods designs). The first phase of qualitative data was taken through in-depth interviews to 5 selected informants using purposive sampling technique. The first phase of the data retrieval was intended to gather information related to the content of character values contained in Â congkak game. All data interviews were analyzed thematically using NVivo qualitative analysis tool 10. Then, the second phase of the data was taken using a questionnaire to 46 students who were studying in grade V and VI in an elementary school (SD). The second phase of the data retrieval was intended to support the first phase of the research results, the entire data of the second phase analyzed descriptively using quantitative analysis tools SPSS Windows 18.0. Overall, the results of the two phases indicated that there were nine character values contained in the game congkak once it was used as a medium of mathematics learning. The nine-character values were honesty, discipline, hard working, creativity, curiosity, independent, communicativeness, responsibility and appreciation for achievements. The results also proved that the use of instructional media such as traditional game congkak can be used as an intermediary that can be used by teachers in mathematics learning process. In addition, this study shows that even though congkak game belongs to a traditional game among middle societies, in fact, there were characters values as it was investigated scientifically.